Modeling and Controlling the Actuator Joint Angle Position on the Robot Arm Base Using Discrete PID Algorithm - Machdiar Rohman; Dede Irawan Saputra (Ultima Computing : Jurnal Sistem Komputer, 2021)
DC motor is a motor that is easy to apply. Its application in robotic DC motor control often occurs errors due to the existing load, so that the DC motor becomes inaccurate. The control used is PID (proportional integral differential). This PID control system works by processing calculations based on the control variables Kp, Ki, and Kd to achieve the conditions according to the expected setpoint. To make a DC motor position control device can be controlled with a PID controller. In practice, the variable to be controlled in this research is position control in the form of degrees. With the Arduino Mega controller, the motor driver as a DC motor rotation controller, the DC motor is given feedback in the form of an encoder sensor, the software used is the Arduino IDE. The results showed that PID control can correct errors and transient responses with a time constant value of 1.50 seconds, a rise time of 1.60 seconds, a settling time of 2.30 seconds and a delay time of 1.20 seconds and a peak time of 1.6 seconds and an error value of 0.33% through tuning parameter Kp = 16 Ki = 0.001 Kd = 16.